Plateholder-Mirror Alignment of Schmidt Telescope - Suganda Jutamulia; Bambang Hidayat (Institute for Research and Community Services (LPPM) ITB, 1981)
Abstract. In the plateholder mirror alignment, we produce an auxiliary point source which falls at the correcting lens. If the adjustment is correct, then the image of once reflection, I1, will coincide with the image of three relections I3, as proposed by Dewhirst and Yates. However our results indicate that, due to off-axis position of the source, there exists aberrations at I1 and I3. Sari. Sebuah sumber-cahaya-titik buatan telah dibentuk pada lensa-koreksi guna tes pelempangan kaset pelat potret Schmidt, di Observatorium Bosscha. Cara Dewhirst dan Yates diadaptasikan untuk keperluan tes. Dalam tes ini, diselidiki jalan berkas cahaya yang terpantul sekali (I1) dan 3 kali (I3) oleh cermin utama. Kalau kedudukan kaset pelat baik, maka I1 akan berimpit dengan I3. Tetapi hasil tes kita memperlihatkan bahwa, akibat kedudukan sumber cahaya di luar sumbu, terjadi aberasi pada I1 dan I3.